Post-cure shape errors of ultra-thin symmetric CFRP laminates: Effect of ply-level imperfections. (15th March 2017) - Steeves, John; Pellegrino, Sergio
Abstract: This paper discusses the effect of misalignments in ply orientation, uniform variations in ply thickness, and through-thickness thermal gradients on the post-cure shape errors for symmetric cross-ply laminates constructed from ultra-thin composite materials. Photogrammetry-based surface measurements are performed for laminates cured at elevated temperatures. Significant out-of-plane shape errors are observed, with amplitudes ∼75 times the laminate thickness. The magnitude of each imperfection is also characterized experimentally on coupon-level samples. A non-linear finite element model is developed and demonstrates that these imperfections result in cylindrical and twisting modes of deformation. Results are compared to Classical Lamination Theory predictions which are shown to be inadequate in predicting shape errors that require changes in Gaussian curvature. Through these studies, it is determined that thickness variations between the top and bottom plies have the most pronounced effect on shape errors.